Povezanost zasićenosti kiseonikom, odnosa neutrofila i limfocita i d-dimera sa kliničkim manifestacijama pacijenata sa COVID-19 - Marwan, Marwan; Khalidi, Muhammad Rizqan; Khotimah, Siti; Wahyunie, Sri; Kalalo, Lili Pertiwi; Gomarjoyo, Fanny (Scripta Medica, 2021)
Background / Aim: Coronavirus 2019 (COVID-19) infection is caused by severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2). It has become an emergency condition for global public health. Oxygen saturation has important role for diagnosing the patient in the hospital. The neutrophil-lymphocyte ratio (NLR) is a marker for the viral inflammatory reaction to confirm the viral or bacterial infection. The D-dimer is also known as biomarker for severity and prognosis of COVID-19. The aim of the study was to investigate the risk factors of mortality in COVID-19 patients based on oxygen saturation, neutrophil-lymphocyte ratio and D-dimer. Methods: Data has been obtained from confirmed cases of COVID-19 in AbdulWahab Sjahranie Hospital from October until November 2020. They were collected and analysed with Chi-squared test by SPSS 22.0 software. Results: There were 60 patients with SARS-CoV-2 infection in this study, 48 (80 %) patients survived and 12 (20 %) deceased. Peripheral oxygen saturation < 90 % had 13 (21.7 %) and ≥ 90 % had 47 (78.3 %) patients. There were 13 (21.7 %) patients with NLR value < 3.13 and ≥ 3.13 47 (78.3 %) patients. D-dimer value less than 0.5 had 9 (15 %) and ≥ 0.5 had 51 (85 %) patients. The results of statistical analysis have showed that there were relationship between oxygen saturation (p = 0.002) and survival rate of COVID patients. Conclusion: According to the research that has been conducted, there was correlation between oxygen saturation and mortality of COVID-19 patient. It could be used as biomarker to improve the management of COVID-19 patients.